Zwitterionic forward osmosis membrane with low structural parameter based on highly porous polyvinylidene fluoride substrate for desalination. (December 2022) - Zhu, Li-Jing; Hu, Yi-Ning; Wang, Yi; Guo, Yan-Feng; Zeng, Zhi-Xiang
Abstract: Polyamide thin-film composites (PA-TFC) forward osmosis (FO) membranes have great potential in wastewater treatment and desalination. However, they are continuously studied to further enhance the FO performances from the improvement of the PA layer and the substrate individually. Here, a polyvinylidene fluoride/poly(hydroxyethyl methacrylate) (PVDF/PHEMA) membrane with a highly porous surface was fabricated and used as the substrate to engineer a thin and rough PA layer. After being post-modified by zwitterionic groups, the resulting membrane (namely TFC90-Z) has a much lower structure parameter ( S, 216 ± 12 µm) in comparison to common FO membranes in literature, thus decreasing internal concentration polarization and increasing FO performances. Specific salt flux ( J s /J w ) and water flux ( J w ) of TFC90-Z are 0.03 ± 0.01 g/L and 18.5 ± 0.4 L m −2 h −1 under the active layer-facing draw solution (AL-DS) orientation using 1.0 M NaCl as the draw solution and deionized water as the feed solution. Meanwhile, NaCl rejection is 91.6 ± 0.1 %. This work offers an efficient way to engineer excellent PA-TFC FO membranes for aqueous separation and desalination. Graphical Abstract: ga1 Highlights: PA-TFC FO membranes were fabricated on highly porous PVDF/PHEMA substrates via IP. The PA layer was post-modified by zwitterionic groups via co-deposition of TA and AEPPS. ICP is weakened due to the low structure parameter of the zwitterionic PA-TFC FO membrane. The as-prepared FO membrane has excellent FO performances especially specific salt flux ( J s /J w ).